2011
DOI: 10.1159/000335106
|View full text |Cite
|
Sign up to set email alerts
|

Pendrin Function and Regulation in <i>Xenopus</i> Oocytes

Abstract: SLC26A4/PDS mutations cause Pendred Syndrome and non-syndromic deafness. but some aspects of function and regulation of the SLC26A4 polypeptide gene product, pendrin, remain controversial or incompletely understood. We have therefore extended the functional analysis of wildtype and mutant pendrin in Xenopus oocytes, with studies of isotopic flux, electrophysiology, and protein localization. Pendrin mediated electroneutral, pH-insensitive, DIDS-insensitive anion exchange, with extracellular K(1/2) (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 71 publications
2
31
0
Order By: Relevance
“…SLC26A3 (DRA/CLD) is a well-characterized chloride/bicarbonate exchanger present in the apical membrane of intestinal enterocytes where it works in conjunction with the NHE3 Na ϩ /H ϩ exchanger to mediate electroneutral NaCl reabsorption by the intestine (10,33,51,55). In addition to bicarbonate and chloride, SLC26A4 (pendrin) can also transport iodide, which may play an important role in the thyroid (12,46,56,57). SLC26A5 (prestin) acts as a voltage-sensitive chloride sensor in the lateral membrane of the cochlear outer hair cell (70).…”
mentioning
confidence: 99%
“…SLC26A3 (DRA/CLD) is a well-characterized chloride/bicarbonate exchanger present in the apical membrane of intestinal enterocytes where it works in conjunction with the NHE3 Na ϩ /H ϩ exchanger to mediate electroneutral NaCl reabsorption by the intestine (10,33,51,55). In addition to bicarbonate and chloride, SLC26A4 (pendrin) can also transport iodide, which may play an important role in the thyroid (12,46,56,57). SLC26A5 (prestin) acts as a voltage-sensitive chloride sensor in the lateral membrane of the cochlear outer hair cell (70).…”
mentioning
confidence: 99%
“…Specifically, Reimold et al describe the function and regulation of pendrin in an heterologous overexpression system, with isotopic flux, electrophysiology, and protein localization methodologies. They confirm the electroneutrality and 4,4'-diisothiocyano-2,2'-stilbenedisulfonic acid (DIDS)-insensitivity of the transporter, show its pH insensitivity and anion selectivity sequence, and identify residues important for activity and regulation [12]. Two original papers in this Special Issue are devoted to assessment of the functionality of wild-type pendrin and several of its allelic variants found in the Palestinian, Israeli and Spanish populations [17,18].…”
Section: Scientific Content Of the Meetingmentioning
confidence: 66%
“…The coupling ratio of the ion exchange was initially unclear; again, considering homology with other members of the same family, and owing to earlier reports, it was assumed that pendrin participated in electrogenic anion exchange [8]. Later, we and others showed that pendrin anion transport was indeed non rheogenic (electroneutral) [9][10][11][12].…”
Section: Scientific Content Of the Meetingmentioning
confidence: 99%
“…7). However, the possible contribution of this STAS domain region to pendrin-mediated electroneutral anion exchange [36,37] remains to be determined.…”
Section: Resultsmentioning
confidence: 99%